Weaning of inhaled nitric oxide: is there a best strategy? - Anita M. Ware; Sergio G. Golombek (Journal of Pediatric and Neonatal Individualized Medicine, 2015)
Background: Inhaled nitric oxide (iNO) has been used in the treatment of pulmonary hypertension in neonates for many years. iNO was approved by the FDA in 1999 for hypoxic respiratory failure (HRF) in term and near term infants, defined as > 34 weeks gestational age (GA). iNO is used for persistent pulmonary hypertension of the newborn (PPHN), secondary pulmonary hypertension caused by congenital heart disease (CHD), congenital diaphragmatic hernia (CDH), meconium aspiration syndrome (MAS), pneumonia, respiratory distress syndrome (RDS), and other pathologies. iNO has its effect locally on the pulmonary vasculature and has been studied extensively regarding its effect on morbidities such as: need for extracorporeal membrane oxygenation (ECMO), oxygen requirements, and mechanical ventilatory support. However, protocols for weaning iNO and for the duration of iNO weaning have not been studied extensively. It has been shown that an abrupt discontinuation leads to rebound pulmonary hypertension.